Development of a lower-extremities exoskeleton for postural-sway in sit-to-stand movement - Lee, Jun Han (2025)
Postural sway, a critical indicator of balance control, is often heightened in individuals with chronic low back pain (CLBP), age-related decline, and neurodegenerative disorders such as Parkinson’s disease. While passive exosuits offer ergonomic support, they lack the capacity for real-time corrective intervention. This project introduces a lightweight, fabric-based active back support exoskeleton powered by pneumatic actuation, designed to detect and correct static postural sway. The system integrates an ESP32 microcontroller, IMU-based sway detection, and a threshold-based control algorithm for real time actuation. The fully assembled prototype was evaluated in 15 subjects across varying stance (normal, tandem) and visual (eyes open/closed) conditions using surface electromyography (sEMG) and centre of pressure (CoP) metrics. Under the most challenging balance condition, Tandem Stance Eyes Closed (TSEC), results showed a 51.5% reduction in CoP pathlength, 27.4% and 41.8% decreases in Vapmean and Vmlmean, and 34.7% and 20.7% reductions in DMLSD and DAPSD, respectively. sEMG analysis indicated a significant drop in trunk muscle activation, with External Obliques (38.3%), Rectus Abdominis (51.2%), and Erector Spinae (L3) Right (41.8%) showing the largest reductions in RMS amplitude during TSEC trials. The sway detection algorithm achieved 70% classification accuracy, supporting low-power, real-time execution on embedded hardware. These findings validate the exosuit’s ability to enhance postural stability and reduce neuromuscular strain during quiet stance. The system demonstrates potential as a practical rehabilitation aid for individuals with CLBP, older adults, or those with early-stage Parkinson’s disease. Future work may involve adaptive control integration and broader clinical validation.